Growth and physiological characteristics of Melaleuca cajuputi Powell planted in contaminated bris soil - Muhamad, Noor Liyana Athirah (2015)
The uses ofsewage sludge as commercial fertilizer in agricultural activities nowadays may resulting the contaminants of groundwater by heavy metals. These heavy metals will flow through the porous medium into groundwater and may cause health problems to all living things. Melaleuca cajuputi had been tested for phytoremediation capabilities using selected heavy metal, i.e. Cu and Zn. Sewage sludge in Malaysia also contains Cu and Zn. The objectives of this study was to determine the heavy metal uptake by Melaleuca cajuputi via transport and leaching losses of solutes using simple lysimeter as well as to investigate the best concentration level of both Cu and Zn for growth and physiological attributes of this species. Totally 72 seedlings were planted in simple lysimeter pots using Beach Ridge Interspersed with Swales (BRIS) soil. A Completely Randomized Design (CRD) was used. Four different level, 0 ppm (control), 100 ppm, 300 ppm, and 500 ppm with nine replications for each treatment were used. After one month planting, growth height, diameter of plants, survival rate,chlorophyll contents and fluorescence, and gas exchange parameters were measured. The growth performances were calculated based on absolute growth rate (AGR) and relative growth rate (RGR). Chemical analyses also were done using AAS methods. Overall observation for physiological and growth performances in the end of study showed that 100 ppm of each Cu and Zn gave the highest and best results for all measurement parameters meanwhile 500 ppm of each Cu and Zn showed the lowest. The results of this study provided some useful information regarding on a better understanding about growth and physiological attributes of the selected plant species which had been proved as a potential plant to remediate contaminated site. Eventhough this study only used the simplest method of lysimeter, it is enough to expose a new and alternative method for planting design that can measure the uptake of heavy metal by plants via leaching losses correspond to phytoremediation purposes.